2007
DOI: 10.1302/0301-620x.89b1.17940
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of pyogenic sepsis of the hip in childhood

Abstract: Between September 2004 and December 2005 we carried out a prospective study of all cases of sepsis of the hip in childhood at a South African regional hospital with a large local population, and which also took referrals from nine rural hospitals. The clinical, radiological, ultrasound and bacteriological features were assessed. All the hips were drained by arthrotomy and the diagnosis was confirmed microbiologically and histologically. Hips with tuberculosis were excluded. The children were reviewed in a dedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0
7

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(51 citation statements)
references
References 26 publications
1
43
0
7
Order By: Relevance
“…Among the patients who had to undergo more than one surgical procedure, there was no relationship between a delayed diagnosis and the time when treatment started. However, based on the literature encountered, it is believed that a delay in treatment may lead to a worse prognosis (2,8,11,12,18,23,24). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the patients who had to undergo more than one surgical procedure, there was no relationship between a delayed diagnosis and the time when treatment started. However, based on the literature encountered, it is believed that a delay in treatment may lead to a worse prognosis (2,8,11,12,18,23,24). …”
Section: Discussionmentioning
confidence: 99%
“…The most common limiting factors for successful treatment are a lack of suspicion of this disease at the initial stages of the symptoms, delay in aspirating the synovial fluid and lack of joint drainage (2,12,13). …”
Section: Introductionmentioning
confidence: 99%
“…Whilst transient synovitis is a benign condition with little potential for long-term serious damage, septic arthritis can lead to a poor outcome, particularly if the treatment is delayed. 7 Kocher, Zurakowski and Kasser 1 initially described several variables to aid in the differentiation of these conditions: temperature > 38.5°C, inability to weight-bear, erythrocyte sedimentation rate (ESR) > 40 mm/hr and peripheral white blood cell count > 12 000 cells/mm 3 . However, in these conditions ESR has largely been replaced by estimation of the C-Reactive Protein (CRP).…”
mentioning
confidence: 99%
“…3 4 A prospective cohort study of all children presenting with septic arthritis of the hip in South Africa found no sequelae among children diagnosed and treated within five days of onset of symptoms, but a very high incidence of permanent problems among those treated at five days or later. 5 Late treatment cannot reverse the damage, caused by pus under pressure and compromised blood flow, to the joint cartilage, the epiphyseal bone, or the growth plate. Unfortunately, more than two thirds of the children in the South African series were treated late, with delay in diagnosis (rather than delay in presentation) the most common reason for delay in treatment.…”
Section: Why Does This Matter?mentioning
confidence: 99%